INEQUALITY TOWARDS WOMEN IN BATTLE OF THE SEXES - Rizal Taufik; Sulistyowati Sulistyowati (PROJECT (Professional Journal of English Education), 2023)
Gender inequality mostly contributes to women having less access than men. This study explores how women are represented unequally in the movie Battle of the Sexes. The data were taken from monologues and dialogues among the characters throughout the movie. Then, we analyzed the data by using Sara Mills' critical discourse analysis (1992). To support the findings, we also categorized forms of gender inequality according to Fakih's theory (2012). The results showed that even though they occasionally can voice their concern, they still struggle to achieve equality since men have more power than them. Additional findings also show that forms of inequality are found except double burden. This study concludes that patriarchal culture holds accountable for this issue. Therefore, if gender inequality still occurs in our society, women will likely have less access to everything and eventually be left behind.Â Keywords:Â  Critical Discourse Analysis; Gender Inequality; Patriarchy; Sara Mills